Role of Mass Media in Development of Urdu Language - Khan, Muhammad Saifullah; Naz, Anum; Mehmood, Nasir (sourcecoder, 2024)
Urdu journalism has played a leading role in the Indian independence movement. It is an honor for Urdu journalism that it has raised its voice against English tyranny and colonialism. The history of India’s independence movement is impossible without Urdu journalism. The hardships of prisons that the editors and journalists of Urdu newspapers endured the most were not borne by the staff of any other language. Let’s look at the history of Urdu journalism. So it is estimated that this art has made significant strides in the promotion of language and literature. The status and popularity of Urdu among the popular languages of India and due to which it has the potential to become a common national language is the medium of journalism. That is why, like all other arts and crafts, it has been given attention in the universities Even the art of journalism has been included in Urdu literature. It is a separate argument that the style of journalism is considered flawed in literature. Urdu literature and journalism have had a deep relationship with each other from the very beginning and of course the media has played an important role in the development and promotion of the Urdu language. Urdu language was reaching the stage of puberty from the time of Kim Sunni. Urdu journalism had started. This was in the early nineteenth century. But now the media is not doing its duty for the development and promotion of Urdu language like the newspapers of the past. The institution of editors has become weak. The media now has not only spelling mistakes but also people who are ignorant of their pronunciation. Have appeared in the media. In spite of the existence of words in Urdu language, they are not being used but English words are being used which are causing the deterioration of Urdu language. In this context, the past efforts for Urdu language are past. The review is presented in the light of current newspapers and domestic and foreign electronic media.